2022
DOI: 10.3390/polym14071417
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Three Commercially Available Desensitizers in Reducing Post-Operative Sensitivity Following Composite Restorations: A Randomized Controlled Clinical Trial

Abstract: One of the most widely used esthetic restorations in dentistry is composite. The widespread application of composites can be related to advancements in biomaterials. However, due to various factors, composites are commonly associated with dental sensitivity. Hence, the present study evaluates and compares the effectiveness of three desensitizing agents in reducing post-treatment sensitivity for Class I composite restoration. Eighty subjects with Class I cavities were selected according to the inclusion criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…But overall Gluma performed better than the control and SAD group. This was in accordance with previous studies conducted by Dondi and Malferrari; Patil et al and Sayed et al confirmed that Gluma desensitizer significantly lead to reduction of postoperative sensitivity [ 13 , 14 ]. Despite these results, no significant difference was observed in the clinical study conducted by Sobral et al with Gluma for any of the stimulus [ 15 ].…”
Section: Discussionsupporting
confidence: 93%
“…But overall Gluma performed better than the control and SAD group. This was in accordance with previous studies conducted by Dondi and Malferrari; Patil et al and Sayed et al confirmed that Gluma desensitizer significantly lead to reduction of postoperative sensitivity [ 13 , 14 ]. Despite these results, no significant difference was observed in the clinical study conducted by Sobral et al with Gluma for any of the stimulus [ 15 ].…”
Section: Discussionsupporting
confidence: 93%
“…The Gluma, Shield Force Plus, and Telio CS desensitizers effectively decrease the post-preparation sensitivity, as has been shown in the study conducted in 2021 by Sayed, M.E. [11]. The same desensitizers were chosen in the present study in order to evaluate their effect on the strength of the bond to the prepared tooth when using selfadhesive resin cement.…”
Section: Discussionmentioning
confidence: 88%
“…The three agents showed varying retentive values: Gluma being the most effective, followed by Shield Force Plus, and then Telio CS. This difference could be due to the differences in their components or their mode of action, their capability to resist dissolution, and the different solubility level of precipitate formation in the dentinal tubules [11]. The hydrophilic properties provided by Hydroxyethyl methacrylate (HEMA) in the Gluma and Shield Force Plus desensitizers improved the bonding to the hydrophilic dentin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations